Evaluation of a Pharmacist-Led Remote Warfarin Management Model Using a Smartphone Application (Yixing) in Improving Patients’ Knowledge and Outcomes of Anticoagulation Therapy - Jiang, Shudan; He, Qiuyi; Yan, Jiajia; Zhao, Liyan; Zheng, Yifan; Chen, Pan; Chen, Xiao (Frontiers in Pharmacology, 2021)
Background: The management of warfarin-treated patients has been recognized as a challenge due to narrow therapeutic range and food and drug interactions in warfarin therapy. We aim to evaluate the effect of a pharmacist-led remote warfarin management model using a smartphone application (app) on anticoagulation therapy. Methods: Eligible patients who had received warfarin therapy after mechanical heart valve replacement for at least 6 months were enrolled. The intervention group was offered a pharmacist-led remote warfarin management model using the app named Yixing. Yixing incorporates functions including automatic daily reminder, personal health record, educational program, and online counseling. The control group received traditional pharmacy services without Yixing. Co-primary outcomes were patients’ awareness score of warfarin therapy obtained from questionnaire, the medication adherence measured by the percentage of the correct-warfarin-taken days in the monitored period, the fraction of time in therapeutic range (FTTR), and the incidence of anticoagulation-related complications. The needed information of the patients was acquired via electronic medical records from the hospital, Yixing system and telephone follow-up when necessary. Results: 64 and 66 patients were initially in the intervention and control groups respectively. After propensity score matching, 50 patients were assigned in each group. The intervention group had a median age of 51.0 years, in which 27 (54%) were male. The control group had a median age of 50.5 years, in which 28 (56%) were male. Patient awareness score in the intervention group was 8.00 (2.00), which was higher than that in the control group, with score at 6.50 (2.50) (P=0.001). No significant difference was found in the percentage of the correct-warfarin-taken days between the two groups (P=0.520). The median (interquartile range) value of FTTR was 80.3% (21.9%) and 72.1% (17.7%) in the intervention and control groups respectively (P=0.033), and no significant differences in the incidence of anticoagulation-related complications were observed (P=0.514). Conclusion: The pharmacists-led remote warfarin management model using Yixing improves patients’ awareness of warfarin therapy and increases FTTR, but may not have significant improvements on medication adherence and safety.